Factors Influencing Subspecialty Training and Career Choices: A National Survey of Physical and Rehabilitation Medicine Residents - Sena TOLU; Aylin REZVANİ and Aysel GÜRCAN ATCI and Ömer Faruk ŞENDUR and Banu KURAN and Şebnem ATAMAN and Hatice BODUR and Jülide ÖNCÜ ALPTEKİN and Erhan ÇAPKIN and Deniz DOĞAN (Archives of Rheumatology, 2019)
Objectives: This study aims to determine the preferences of physical and rehabilitation medicine (PRM) residents in Turkey for future career choices, subspecialty training plans, and practice location and to identify the factors that influence those preferences. Materials and methods: Using a cross-sectional study design, a survey was sent to all PRM residents enrolled in the Turkish Society of Physical Medicine and Rehabilitation and the Turkish League Against Rheumatism (n=500). A total of 181 residents (36%) (74 males, 107 females; mean age 28.8 years; range 24 to 40 years) responded to the survey. Data were collected about demographic profile of respondents and PRM clinics, respondents’ experiences in rheumatology education and injection skills, preferences for fellowship training, and future practice location. Results: Thirty-five percent of residents intended to pursue fellowship training. Rheumatology was more preferred than algology. Male sex was positively associated with the decision to pursue fellowship training and also having an algology division in the PRM department was positively associated with planning to pursue algology fellowship training. For those planning to pursue fellowship training, the most influential factors were prestige, interest in an academic career and the possibility of performing compulsory service in a better location. Thirty-four percent of residents preferred to work in university hospitals after residency while 57% of residents who planned to pursue fellowship training preferred to practice at university hospitals after their fellowship. Thus, an academically oriented career was the most desirable career choice. Conclusion: One-third of residents training in Turkey chose to pursue fellowship training and work in university hospitals. Performing compulsory service was the top factor affecting the decisions of both undecided and reluctant residents; thus, career plans of PRM residents in Turkey are not based solely on personal and professional desires, but require consideration of compulsory service.